The study of the electrical activity of the rectus femoris muscle in scoring skill of jumping Amama Hand Reel - Ghazi, Abedulwahab; Talib, Hadeel (Journal of Physical Education, 2015)
The study of the electrical activity of the muscle rectus femoris variables enables the coach to know the muscle groups responsible for the motor to be, which is reflected on the training and then at the level of performance and the importance of research in the possibility of finding the relationship between indicators that can be obtained from the EMG device (space, Summit), which is inferred through which the electrical signal strength and motor units associated with the work of the working muscle and associated variables during the implementation of the scoring. The research problem lies in the study of the relationship of the electrical activity of the rectus femoris muscle and its relationship to scoring Amama.a The aim of the research is to identify the electrical activity of the rectus femoris muscle and its relationship to scoring Amama hand reel. The imposition of research there is a significant relationship between the electrical activity of the muscle rectus femoris and accuracy scoring hand reel either Part II Vahtoy on the electrical layout of the muscles and the rectus femoris and the scoring of jumping imam, and the researcher used the descriptive method on a sample of players applicants hand reel and the number (10) as it has been selected in a manner Part IV intentional. As the researcher used the statistical pouch (SPSS) was discussed, depending on the results of scientific sources. In Part V researcher concluded that the study of the evolution of the activity between the electrical activity of the muscles working. The researcher recommended to the attention of coaches when developing training programs using scientific methods on the basis of the results of the tests adopted as a case of training and knowledge to assess the health status of athletes